Subject:
MathematicsAuthor:
silkyCreated:
7 months agoAnswer:
D
Step-by-step explanation:
x/(x²+3x+2) - 1/[(x+2)(x+1)]
x² + 3x + 2 = x² + 2x + x + 2
= x(x + 2) + (x + 2)
= (x + 2)(x + 1)
= x/[(x+2)(x+1)] - 1/[(x+2)(x+1)]
= (x-1)/[(x+2)(x+1)]
= (x-1)/(x²+3x+2)
Author:
schnookums0usk
Rate an answer:
18The difference of rational polynomial function is \frac{x-1}{x^{2} +3x+2}
Given expression is,
\frac{x}{x^{2} +3x+2}-\frac{1}{(x+2)(x+1)}
(x+2)(x+1)=x^{2} +2x+x+2=x^{2} +3x+2
Given expression can be written as,
\frac{x}{x^{2} +3x+2}-\frac{1}{x^{2} +3x+2} =\frac{x-1}{x^{2} +3x+2}
Author:
melanyg0ac
Rate an answer:
10Rate an answer:
0Don't worry! There are several alternative approaches you can try to resolve your query. Here are some tips to help you find answers in different ways:
Remember, the process of finding answers often involves persistence, creativity, and an open mind. By exploring various resources, reaching out to others, and being proactive in your search, you increase your chances of finding the information you need. Happy quest for knowledge!